Membangun Pesantren Personal: Regulasi Diri Santri Tuna Netra dalam Menghafal Al-Qur'an Pasca Lulus dari Pesantren - Riza Kurniawan (Advances In Education Journal, 2026)
This study explores the self-regulation dynamics of visually impaired pesantren alumni in maintaining Quranic memorization during their transition to society. Using a qualitative phenomenological approach with four informants, the research identifies that the loss of institutional support structures poses a significant challenge to consistency. Results reveal a spiritual coping mechanism where blindness is perceived as a protective shield against sin, bolstering intrinsic motivation. The key finding highlights the "Membangun Pesantren Personal” to internalizing the pesantren environment strategy as an effective self-regulation model. This includes self-indoctrination to foster discipline, utilizing audio technology for positive isolation from environmental distractions, and proactively seeking social support. The study concludes that independence and technological adaptation are primary determinants for alumni to remain guardians of Quranic values in a heterogeneous society. These implications underscore the necessity for post-graduation readiness programs in disability-inclusive Islamic institutions.